Variação em pequena escala da macrofauna bentônica em uma planície de maré do estuário do Rio Pacoti - Ceará, Brasil - Silva, Aline Ferreira da (2017)
In estuarine environments, the interaction between spatial and temporal variations controls the abundance and diversity of benthic organisms. The features of the benthic environment, as well fauas the faunistic variability, can be studied in different scales, being considered small-scale phenomena those that characterize areas of tens of m2 or less. The aim of the present research was to assess benthic macrofauna structure and correlate it to the environmental conditions in a tidal flat on Pacoti River estuary. In February of 2005, a tidal flat area of 30x30 m was marked and subdivided in 9 areas of 10x10 m. The area presented high faunistic similarity, showing that species were distributed depending on the sediment characteristics (grain selection and the percentage of calcium carbonate and organic matter), thereby defining the formation of aggregates (spots) of the most abundant species, although they were weakly discriminated. Small-scale spatial features determined distinct conditions for the macroinfauna distribution, reinforcing the close relationship of benthic organisms to sediments and describing a pattern of distribution in the area that would not be understood in horizontal meso-scale assessments.